2011
DOI: 10.5897/ajb10.1899
|View full text |Cite
|
Sign up to set email alerts
|

The effects of drip line depths and irrigation levels on yield, quality and water use characteristics of lettuce under greenhouse condition

Abstract: This study was conducted to investigate the effects of different drip irrigation methods and different irrigation levels on yield, quality and water use characteristics of lettuce (Lactuca sativa var. longifolia cv. Lital) cultivated in a solar greenhouse from 07 October 2009 to 03 December 2009 in the Eastern Mediterranean region of Turkey. The irrigation methods were consisted of traditional surface drip irrigation (TDI), subsurface drip irrigation at 10 cm drip line depth (SDI 10) and subsurface drip irriga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…On the other hand, researchers found that at pH 5, the shoot and root weight was excellent, but with higher pH (above 7) these values were lower [82]. Moreover, total dissolved solids should also be monitored because high levels (above 1000 mg/L) can impair plant growth [83].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, researchers found that at pH 5, the shoot and root weight was excellent, but with higher pH (above 7) these values were lower [82]. Moreover, total dissolved solids should also be monitored because high levels (above 1000 mg/L) can impair plant growth [83].…”
Section: Discussionmentioning
confidence: 99%